Twinning “Practices of Change” With “Theory of Change”: Room for Emergence in Advocacy Evaluation - and Arensman, Bodille; van Waegeningh, Cornelie; van Wessel, Margit (American Journal of Evaluation, 2018)
Theory of change (ToC) is currently the approach for the evaluation and planning of international development programs. This approach is considered especially suitable for complex interventions. We question this assumption and argue that ToC’s focus on cause–effect logic and intended outcomes does not do justice to the recursive nature of complex interventions such as advocacy. Supported by our work as evaluators, and specifically our case study of an advocacy program on child rights, we illustrate how advocacy evolves through recursive interactions, with outcomes that are emergent rather than predictable. We propose putting “practices of change” at the center by emphasizing human interactions, using the analytical lenses of strategies as practice and recursiveness. This provides room for emergent outcomes and implies a different use of ToC. In this article, we make a clear distinction between theoretical reality models and the real world of practices.